Revolutionizing Diabetes Treatment with Insulin-loaded Nanoparticles - Vats, Jatin; Rana, Anjali; Chauhan, Ajesh; Rajput, Shivam; Malviya, Rishabha; Vashist, Chetan; Mittal, Arun; Sridhar, Sathvik Belagodu (Mini Reviews in Medicinal Chemistry, 2025)
Diabetes mellitus is a disease characterised by elevated blood glucose levels, with its major subtypes being type 1 (immune-mediated) and type 2 (lifestyle-related) diabetes. Medical treatment for diabetes requires patients to perform subcutaneous insulin injections since oral insulin faces problems with gastric breakdown. Nano-sized insulin delivery systems show great potential for oral usage because they protect the insulin molecule from enzymatic breakdown and enhance its absorption rates through the digestive system. The review article investigates the utilisation of insulin-loaded nanoparticles as an advanced treatment method for diabetes management. The data evaluates insulin-loaded nanoparticles for their impact on stability enhancement as well as their protective functions and improved oral bioavailability potential. The research reviewed the relevant literature on insulin-loaded nanoparticles as a treatment method for diabetes. The research articles were obtained through databases including ScienceDirect, Scopus, PubMed and Google Scholar. Studies about incorporating insulin with nanoparticles and their bioavailability features and therapeutic potential were analysed. The review demonstrates that insulin-loaded nanoparticles markedly improve insulin stability, bioavailability, and absorption, overcoming the challenges associated with oral insulin delivery. Diverse nanoparticle compositions, encompassing polymeric and lipid-based carriers, exhibit encouraging outcomes in preclinical investigations. Despite existing limitations in large-scale production and clinical application, nanotechnology presents a revolutionary method for diabetes treatment. Additional research and clinical studies are necessary to validate insulin-loaded nanoparticles as a feasible, patient-friendly substitute for traditional insulin therapy.
Keywords: nanotechnology